Macroinvertebrate assemblages in streams and rivers of a highly developed region (Lake Taihu Basin, China) - Y Zhang (Inter-Research, 2014)
The Lake Taihu Basin, one of the most highly developed regions in China, suffers from severe water pollution and habitat degradation as a result of economic development and urbanization. However, little research has been conducted on the benthic macroinvertebrate assemblages and their environmental relationships. We studied the community structure of benthic macroinvertebrates in this area and explored possible factors regulating their structure, diversity, and distribution. We recorded a total of 104 taxa; Bellamya aeruginosa had the highest frequency of occurrence (71 out of 93 sites), followed by Limnodrilus hoffmeisteri (49) and Corbicula fluminea (42). Oligochaeta was the most abundant taxonomic group, accounting for 89.42% of total macroinvertebrate abundance. Benthic communities were mainly characterized by pollution-tolerant taxa, such as L. hoffmeisteri (Oligochaeta), B. aeruginosa (Gastropoda), and Polypedilum scalaenum (Chironomidae), indicating severe anthropogenic disturbance and habitat degradation. The macroinvertebrate diversity decreased from the western hills to the eastern plains aquatic ecoregions; the Shannon-Wiener and Margalef indices differed significantly between the two ecoregions. The abundances (%) of gathering collectors increased from upstream to downstream, but scrapers showed the opposite trend, consistent with the river continuum concept. Community structure and spatial patterns of macroinvertebrates in the Lake Taihu Basin were strongly correlated with habitat diversity, nutrient loads, and aquatic vegetation coverage. These results provide valuable information for effective management practices of biodiversity conservation in stream and river ecosystems of the Lake Taihu Basin.